Ventricular septal defect in octogenarian: a case report - Das, Sunil Kumar; Shah, Nischal; Pariyar, Bijaya; Yadav, Manish (Journal of General Practice and Emergency Medicine of Nepal, 2023)
It is not a common case that we see in our day-to-day clinical practice, a patient presenting with congenital VSD at the age of eighty. Ventricular septal defect (VSD) is a developmental defect of the interventricular septum resulting from a deficiency of growth or a failure of alignment or fusion of component parts of ventricular septum.1 Ventricular septal defects are the most common form of congenital heart disease and among the most frequently seen congenital abnormalities.2Perimembranous defects are the most common types of ventricular septal defects and account for 80% of such defects.3 It is estimated that 25–40% of VSDs will close by the age of 2 years, and they are unlikely to persist after the age of 10 years; thus adults with congenital heart disease, VSDs represent only about 10% of the cases.